P-122 Optimising IUI; a systematic review and network meta-analysis. (30th June 2022) - Chronopoulou, E; Shaikh, S; Gaetano-Gil, A; Raperport, C; Tsiveriotis, K; Al Wattar, B.H; Zamora, J; Bhide, P
Abstract: Study question: What is the effectiveness of add-on interventions to the standard intra-uterine insemination (IUI) protocol in improving reproductive outcomes? Summary answer: Amongst the add-ons studied only luteal phase support and endometrial scratch were found beneficial for (LBR)/ongoing pregnancy rate (OPR) in IUI cycles. What is known already: IUI is a fertility treatment offered to couples and single women for varied indications worldwide. Although cheaper and less invasive than in-vitro fertilization (IVF), it has received less attention and success rates remain low. Various add-ons have been introduced to boost IUI outcomes. However, their use remains largely empirical and is not standardized. Exploring the effectiveness of different protocol add-ons in comparisons with each other and with the standard protocol, could help develop evidence-based recommendations and optimize IUI treatment. Study design, size, duration: We conducted a systematic review and meta-analysis aiming to assess the value of various IUI add-ons on clinical outcomes (PROSPERO registration number CRD42022300857). A computerized literature search was performed using EMBASE, MEDLINE, CINAHL and the Cochrane Central from database inception to October 2021. Two authors independently assessed the studies for quality and risk of bias. Studied add-ons included use of hydrotubation, endometrial scratch, trigger, double insemination, ultrasound guidance, bed rest, tocolysis and luteal phase support. Participants/materials, setting, methods: Randomized controlled trials (RCTs) were included, reporting on one or more cycles of IUI with any protocol and indication using partner's or donor sperm. We summarized the LBR or OPR when LBR was not available. We calculated odds ratios with 95% confidence intervals (CI) using random effects meta-analysis after transforming data using Freeman-Tukey double arcsine transformation. Heterogeneity was reported as I 2 and Tau 2 estimates. Main results and the role of chance: Sixty one RCTs were included in the analysis. Amongst the add-ons studied, luteal phase support and endometrial scratch were found to increase chance of LBR/OPR by 1.48 times (CI 1.1243-1.9402, I 2 = 13.3%, Tau 2 = 0, 0156 p = 0.330) and 1.58 times (CI 1.0992-2.2685, I 2 = 0.0%, Tau 2 =0, 00 p = 0.510) respectively. No statistically significant difference was found for the use of hydrotubation (pooled OR 1.4192, CI 0.4936 - 4.0804, I 2 = 67.3%, Tau 2 =0, 57 p = 0.047), trigger (pooled OR 0.6649, CI 0.2422- 1.8257, I 2 = 74.7%, Tau 2 =0, 3972, p = 0.047), hCG versus agonist trigger (pooled OR 1.1570, CI 0.7501- 1.7847, I 2 =0.0%, Tau 2 =0.00, p = 0.502), ultrasound guidance (pooled OR 2.119, CI 0.8289-5.3809, p = 0.437), double IUI (pooled OR 0.9718, CI 0.5721-1.6508, I 2 =0.0%, Tau 2 =0.00, p = 0.567), and bed rest (pooled OR 1.1459, CI 0.4789-2.7418, I 2 =0.0%, Tau 2 =0.00, p = 0.005). No eligible studies were found on tocolytic agents. Two studies were identified for the use of misoprostol but the authors do not report results on the outcomes of interest. Limitations, reasons for caution: The risk of bias was considered as "high"/"some concerns" for all included studies and the overall quality of evidence is low. Included studies randomized both per woman and per cycle and significant differences were noticed in ovarian stimulation protocols. More well-designed RCTs are needed in order to reach sound conclusions. Wider implications of the findings: This meta-analysis provides evidence that luteal phase support and endometrial scratch provide clinical benefit for IUI success rates. However, it is possible that different add-ons could benefit specific patient groups. There is place for more research in the field to explore the value of add-ons in relation to subfertility background. Trial registration number: n/a